Study of Mataya Festival from Communication Perspective (Bodhi: An Interdisciplinary Journal, 2024)
This study first presents an overview of the Mataya festival followed by an analysis of its various signs and components using communication theory, providing an exploration into the communicative tradition of the festival. The study demonstrates how Mataya communicates its signs to enable the feeling of Sahridayata or oneness as envisioned in Adhikary’s Sadharanikaran Model of Communication (SMC). The process of Sadharanikaran is applicable in all sentient beings towards orienting themselves to the attainment of Buddhahood. It ultimately presents how Mataya functions as a medium for fostering social harmony in the heterogenous society of Patan through its universally desired message for alleviation of suffering attained by following the Buddha’s guidance